2015
DOI: 10.1017/s0021932015000206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nativity and Duration of Residence on Chronic Health Conditions Among Asian Immigrants in Australia: A Longitudinal Investigation

Abstract: This study examined the effect of Asian nativity and duration of residence in Australia on the odds of reporting a chronic health condition (cancer, respiratory problems, cardiovascular disease (CVD) and diabetes mellitus). Data were from waves 3, 7 and 9 of the Household Income and Labour Dynamics in Australia (HILDA) longitudinal survey, and multi-level group-mean-centred logistic regression models were used for the analysis. After covariate adjustment, Asian immigrants were less likely to report cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 47 publications
10
34
1
Order By: Relevance
“…However, most of these studies compared migrants with 10–15 years of residence with those who had a shorter residence, whereas our study compared between migrants with 15–30 years and >30 years of residence. Consistent with our study, Pasupuleti et al 25 found no differences in self-reported CVD between migrants with and without at least 20 years of residence. However, other studies examining longer periods of residence have reported convergence or divergence of CVD risk 8 26.…”
Section: Discussionsupporting
confidence: 93%
“…However, most of these studies compared migrants with 10–15 years of residence with those who had a shorter residence, whereas our study compared between migrants with 15–30 years and >30 years of residence. Consistent with our study, Pasupuleti et al 25 found no differences in self-reported CVD between migrants with and without at least 20 years of residence. However, other studies examining longer periods of residence have reported convergence or divergence of CVD risk 8 26.…”
Section: Discussionsupporting
confidence: 93%
“…There is a large body of evidence supporting these trends, with studies conducted in the Australian context 8,9 and other countries 10 reporting that immigrants are less likely to have a chronic condition in comparison to the host population, and that rates of chronic conditions among immigrants converge to that of the host population with increased duration of residence. That said, a study conducted in the Australian context among Asian immigrants examined the influence of nativity and duration of residence on a range of chronic conditions and reported that these trends may be dependent on the health condition 11 …”
mentioning
confidence: 99%
“…That said, a study conducted in the Australian context among Asian immigrants examined the influence of nativity and duration of residence on a range of chronic conditions and reported that these trends may be dependent on the health condition. 11 A study by Marmot and colleagues examined the differences in chronic disease among Japanese men in three different contexts (Japan, California, Hawaii) and found those of Japanese origin living in California had the highest prevalence of coronary heart disease (CHD), with the lowest rates observed among those living in Japan. 12 These findings may suggest that the prevalence of chronic disease differs among ethnic groups of the same origin living in different contexts due to the unique exposures associated with each destination country.…”
mentioning
confidence: 99%
“…Although migrants are generally healthier than their native-born peers due to the health restriction policies for migration, these advantages are likely to attenuate with the years of stay in Australia (21), It is important to understand the risk behaviours and the determining factors of such risk health behaviours in ethnic minority groups. This is the first study that aimed to identify the knowledge, attitudes and practices relating to antibiotic use, and the potential correlates to inappropriate antibiotic use in this group.…”
Section: According To the Work Of The Joint Expert Technical Advisorymentioning
confidence: 99%
“…International literature reveals that risk factors including age, gender, occupational impact, rural residence and presence of chronic diseases, were related to selfmedication with antibiotics (64,68,69,78 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and older (50-64) age were at higher risk of self-medication with antibiotics. The findings also varied upon whether males or females would have a higher prevalence of self-medication (68,79,80).…”
Section: Associated Factors For Self-medication With Antibioticsmentioning
confidence: 99%